2013
DOI: 10.3324/haematol.2013.094474
|View full text |Cite
|
Sign up to set email alerts
|

Early lesions of follicular lymphoma: a genetic perspective

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nposed to distinguish FLIS from partial involvement by FL (PFL). In PFL there is greater architectural distortion, and the diagnosis of lymphoma is more evident histologically. However, interestingly, patients with PFL appear to present with low-stage disease, with a relatively low risk of progression and often a very prolonged disease-free interval with limited therapy. 12 Thus, PFL may represent a bona fide early stage in the biological evolution of FL, and not j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 51 publications
6
66
0
6
Order By: Relevance
“…Two recent high-resolution array CGH studies of FLIS/FLBUS identified a paucity of genetic aberrations in comparison with FL, supporting the conclusion that these lesions are at a very early stage of evolution, and do not represent merely seeding of germinal centers by lymphoma at a distant site. 42,43 Of note, evidence for EZH2 mutations, thought to occur early in follicular lymphomagenesis, were found in both reports. Duodenal follicular lymphoma (DFL) showed a similar low level of aberrations, while PFL appeared to represent an intermediate stage of evolution.…”
Section: E Fmentioning
confidence: 93%
See 2 more Smart Citations
“…Two recent high-resolution array CGH studies of FLIS/FLBUS identified a paucity of genetic aberrations in comparison with FL, supporting the conclusion that these lesions are at a very early stage of evolution, and do not represent merely seeding of germinal centers by lymphoma at a distant site. 42,43 Of note, evidence for EZH2 mutations, thought to occur early in follicular lymphomagenesis, were found in both reports. Duodenal follicular lymphoma (DFL) showed a similar low level of aberrations, while PFL appeared to represent an intermediate stage of evolution.…”
Section: E Fmentioning
confidence: 93%
“…50 High resolution array CGH analysis has shown that DFL shares genomic aberrations with FLIS and PFL suggesting common pathways of origin. 42 However, unlike in PFL, a large fraction of these alterations were not shared with FL. In the context of reduced AID expression in DFL, these aberrations could have occurred before downregulation of AID or independent of it.…”
Section: Primary Duodenal Follicular Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Pour répondre à cette question, nous avons créé un modèle murin dont l'objectif était de récapituler le plus fidèlement possible les étapes précoces de progression du lymphome folliculaire, depuis l'expression sporadique de la translocation t(14;18) chez l'individu sain (dans ~ 1 cellule sur 1 million) jusqu'aux formes les plus pré-coces, telles que le « lymphome folliculaire in situ » (FLIS). Le FLIS est considéré comme l'entité clinique la plus précoce du lymphome folliculaire ; celle-ci se manifeste par une colonisation partielle des centres germinatifs (en général quelques foci BCL2 + au sein de centres germinatifs normaux par ailleurs, BCL2 -, sans distorsion architecturale), et progressant vers un lymphome folliculaire dans ~ 5 % des cas [9]. Dans notre modèle nommé un marqueur spécifique de chaque clone (clonotypique) se substituant au point de cassure de t(14;18).…”
Section: Une Hypothèse De Travailunclassified
“…6 Exome-seq : séquençage de l'exome à haut débit. [9]. De plus, une excellente correspondance existe entre le taux et la relevance/récurrence des altérations et les différents stades de progression vers le lymphome folliculaire (FLIS < lymphome folliculaire bas grade < lymphome folliculaire haut grade).…”
Section: Une Hypothèse De Travailunclassified